Shoulder ultrasound imaging in the post-stroke population: a systematic review and meta-analysis - Ting-Yu Lin; Peng-Chieh Shen; Ke-Vin Chang; Wei-Ting Wu; Levent Özçakar (Medical Journals Sweden, 2023)
Objective: Post-stroke shoulder pain is a serious challenge for stroke survivors. The aim of this meta-analysis was to review the literature to confirm information on structural changes in post-stroke shoulders detected by ultrasound examination. Methods: PubMed, Embase, Web of Science and ClinicalTrials.gov were searched until 7 December 2022, for studies describing shoulder sonographic findings in stroke patients. Two independent authors selected the studies, extracted the data, and performed the critical appraisal. Results: A total of 23 clinical studies were included. The most prevalent pathologies in hemiplegic shoulders pertained to the biceps long head tendon (41.4%), followed by the supraspinatus tendon (33.2%), subdeltoid bursa (29.3%), acromioclavicular joint (15.0%), and subscapularis tendon (9.2%). The common pathological findings encompassed bicipital peritendinous effusion (39.2%), biceps tendinopathy (35.5%), subdeltoid bursitis (29.3%) and supraspinatus tendinopathy (24.6%). Biceps long head tendon and supraspinatus tendon abnormalities were observed significantly more in the hemiplegic (vs contralateral) shoulders, with odds ratios of 3.814 (95% confidence interval 2.044-7.117) and 2.101 (95% confidence interval 1.257-3.512), respectively. No correlation was observed between motor function and shoulder pathology. Conclusion: Ultrasonography enabled the identification of common shoulder pathologies after stroke. Further research is needed to establish the association between these changes and the clinical course of stroke patients.